2020
DOI: 10.3892/ol.2020.11490
|View full text |Cite
|
Sign up to set email alerts
|

High expression of lncRNA-SNHG7 is associated with poor prognosis in hepatocellular carcinoma

Abstract: Expression of long non-coding RNA SNHG7 (lncRNA-SNHG7) and its clinical significance in hepatocellular carcinoma (HCC) were explored. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect the expression level of lncRNA-SNHG7 in cancer tissues. Kaplan-Meier curves and multivariate Cox proportional models were used to study the impact on clinical outcome. Expression of lncRNA-SNHG7 was much higher in cancer tissues than that in para-cancer tissues. The lncRNA-SNHG7 expression was correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…We found that over-expression of SNHG12 and SNHG20 in LIHC ( Figure 3 ) had significant alteration across cancer stages, representing their roles in cancer progression and invasion. These lncRNAs identified in our study were previously reported in their corresponding cancers ( Yang et al, 2015 ; Zhang et al, 2016 ; Li et al, 2019 ; Tamang et al, 2019 ; Feng et al, 2020a ; Niu et al, 2020a ; Martinez-Barriocanal et al, 2020 ; Shen et al, 2020 ; Zeng et al, 2020 ; Zhang et al, 2020b ; Zheng et al, 2020 ) but a comprehensive investigation of distinct or shared lncRNAs in these cancers has not yet been conducted.…”
Section: Discussionsupporting
confidence: 51%
“…We found that over-expression of SNHG12 and SNHG20 in LIHC ( Figure 3 ) had significant alteration across cancer stages, representing their roles in cancer progression and invasion. These lncRNAs identified in our study were previously reported in their corresponding cancers ( Yang et al, 2015 ; Zhang et al, 2016 ; Li et al, 2019 ; Tamang et al, 2019 ; Feng et al, 2020a ; Niu et al, 2020a ; Martinez-Barriocanal et al, 2020 ; Shen et al, 2020 ; Zeng et al, 2020 ; Zhang et al, 2020b ; Zheng et al, 2020 ) but a comprehensive investigation of distinct or shared lncRNAs in these cancers has not yet been conducted.…”
Section: Discussionsupporting
confidence: 51%
“…In recent years, according to detecting the tissues and plasma of cancer patients by real-time reverse transcription-polymerase chain reaction (RT-PCR), a high quantity of aberrantly expressed lncRNAs is found to participate in tumor metabolism to promote tumor development in different ways [57]. It has been found that only 1.5% of nucleic acid sequences were coding that is they make proteins while the rest 98.5% of the sequences are noncoding RNAs in three billion base pairs of the human genome, the latter regulated gene expression and maintained intracellular homeostasis through chromosome alteration, regulation of transcription, Zhang 2020 [28] Zhang 2020 [29] Dong 2016 [24] Shi 2015 [25] Shen2020 [27] Jiao2020 [30] Xiao2020 [31] Zeng2019 [53] Bai2019 [54] Nie2019 [33] Fu2019 [34] Zhao2019 [35] Pan2019 [36] Wang2019 [37] Guo2019 [38] Wang2019 [39] Zhou2019 [41] Yu2020 [42] Huang2018 [43] Jin2018 [46] Li2018 [48] Zeng2018 [51] Liang2021 [52] Overall, DL (I 2 = 0.0%, p = 0.829) Overall, IV and posttranscriptional regulation. LncRNA dysregulation can cause chromosome loss and translocation, leading to the occurrence of cancer [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Cox regression analyses confirm the predictive value of SNHG7 as an independent prognostic factor among cancerous patients. This is particularly reported in several district experiments on human malignancies such as gastric cancer, cervical cancer, HCC, and liver metastasis following hepatectomy in CRC patients ( Table 2 ) ( Zeng et al, 2019 ; Zhang et al, 2020a ; Zhang et al, 2020c ; Shen et al, 2020 ). As for diagnostic values, an area under curve (AUC) of 0.84 in the receiver operating characteristic (ROC) curve is reported for SNHG7 in CRC patients ( Hu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 70%